IDEOLOGI ‘KANCA WINGKING’: STUDI RELASI KUASA PENGETAHUAN DALAM TAFSIR ALHUDA - Suci Wulandari (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2018)
The Qur’anic interpretation which is done by a mufassir, ideally must be free from various interests, personally or even politically. Factually a mufassir often carries particular interest in their interpretation processes, whether it is done consciously or not. Bakri Syahid, as a mufassir was not able to be free from the political interests that supporting New Order government when he interpreted Alquran. This can be clearly seen in his interpretation of the verses about women. Based on the theoretical analysis of Michel Foucault's power of knowledge, this study revealed that Bakri Syahid interpretation on the verses about women in Tafsir Alhuda showing the Javanese ideological influence, which is positioned women as ‘kanca wingking’ or complementary behind their husbands, and also the 'hidden' power; namely the affirmation of women position listed in national regulation No. 1, 1974 about marriage. This result also confirmed that the product of interpretation could not be completely free from the mufassir interests, and even could be a "mirror" for the government political interests in certain time.